K-Ar isotopy data of deformed samples from the Yushu mélange, western Jinsha Suture - Fanny Goussin; Stéphane Guillot; Gilles Ruffet; Marc Poujol; Émilien Oliot; Anne Replumaz; Carole Cordier; Guillaume Dupont-Nivet; Pierrick Roperch (PANGAEA, 2021)
Deformed samples from the Yushu mélange, in the western Jinsha Suture, have been dated by 40Ar/39Ar isotopy on micas and/or amphibole. Rock samples were crushed using standard procedures. Individual grains were handpicked from the 0.5-1-millimeter fraction of the crushed samples. Samples were irradiated in three batches, IR24, IR26 and IR36, at McMaster Nuclear Reactor (Hamilton, Ontario, Canada - https://nuclear.mcmaster.ca/facilities-equipment/facility-list/mcmaster-nuclear-reactor/) in its 8E high neutron flux facility. IR24 IR26 and IR36 lasted 50.967h, 50h and 200.95h with global efficiencies (J/h) of 4.97 x 10-5, 8.25 x 10-5 h-1 and 1.03 x 10-4 h-1. The analytical procedure is described by Ruffet et al. (1991, 1995). The irradiation standard were sanidine TCRs (28.608 ± 0.033 Ma according to Renne et al., 2011) for irradiation IR24 and IR26 and amphibole Hb3gr (1081.0 ± 1.2 Ma according to Renne et al., 2011) for irradiation IR36. Blanks were performed routinely each first or third/fourth run, and are subtracted from the subsequent sample gas fractions. Errors of apparent ages are plotted at the 1σ level and do not include the errors on the 40Ar*/39ArK ratio and age of the monitor and decay constant. The errors on the 40Ar*/39ArK ratio and age of the monitor and decay constant are included in the final calculation of the error margins on the pseudo-plateau and plateau ages. 40Ar/39Ar ages are provided with 2σ errors. Analytical data and parameters used for calculations (e.g. isotopic ratios measured on pure K and Ca salts; mass discrimination; atmospheric argon ratios; J parameter; decay constants) and reference sources are available in Table "Parameters used for Ar-Ar data analysis".